THE DIRECTED USING OF THE BEE COLONIES WITH THE ALTERED PHYSIOLOGICAL STATE - Гречка, Г. М. (Scientific Progress & Innovations, 2014)
There has been shown the possibility of intensification of economic activity of the bee colonies with the presence of swarming features by applying three methods of beekeeping: the shuffling of the nest, the nest renovation, the artificial division of bees. It has been proven that “the nest renovation" is an optimal method of beekeeping which helps to normalize the physiological state of the colonies of honey bees (from swarming to working). return to normal life, stabilize and use their swarming energy efficiently in the complex beekeeping and increase the productivit: honey - 12% , wax - 15% .